A palaeoclimate proxy database for water security planning in Queensland Australia - Jacky Croke (Nature Portfolio, 2021)
Measurement(s) climate Technology Type(s) digital curation Factor Type(s) proxy type • geographic location • temporal interval • environmental material Sample Characteristic - Environment climate system Sample Characteristic - Location Earth (planet) Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.16607162